Inbreeding avoidance, competition and natal dispersal in a pair-living, genetically monogamous mammal, Azara’s owl monkey ( Aotus azarae ) - Corley, Margaret (2024)
Natal dispersal is an important life-history stage influencing individual fitness, social dynamics of groups and population structure. Understanding factors influencing dispersal is essential for evaluating explanations for the evolution and maintenance of social organization, including parental care and mating systems. The social and mating systems of Azara’s owl monkeys (Aotus azarae) are infrequent among mammals; these primates are pair-living, serially and genetically monogamous and both sexes directly care for offspring. To evaluate the role that competition and inbreeding avoidance play in shaping dispersal patterns, we used 25 years of demographic and genetic data to examine how variation in timing of natal dispersal is related to social (adult replacements, step-parents, births and group size) and ecological factors (seasonal abundance of resources) in a wild population of A. azarae in Formosa, Argentina. We found that all males and females dispersed from their natal groups, but subadults delayed dispersal when a step-parent of the opposite sex joined the group, indicating that they may perceive these step-parents as potential mates. Dispersal was more probable when resource conditions were better, regardless of age. Overall, agonistic conflict over food and potential mates with adults in the natal group, as well as inbreeding avoidance, contribute to regulating dispersal.